4TH UCEC KICKS OFF IN GOLD COAST, AUSTRALIA - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
GOLD COAST, AUSTRALIA, 2 November 2015 The 4 University Community Engagement Conference (UCEC) started off with a welcoming reception for the delegates at the Currumbin Wildlife Sanctuary here last night.